Strutture comunicative e intersoggettività in Husserl - Costa, Vincenzo (Bollettino Filosofico, 2022)
In this paper I try to highlight the different ways in which the structure of intersubjectivity can be explored. This topic can be investigated by a static, a fictitious genetic and an effective genetic analysis. Discussing the second one I explore the link between of forms of communication, levels of intersubjective constitution and layers of self-consciousness is investigated in Husserl’s work. Keywords: Communication Structures, Empathy, Intersubjectivity, Husserl, Self-Consciousness